ANALISIS OPTIMALISASI POJOK BACA DALAM MENINGKATKAN MINAT BACA ANAK USIA DINI: STUDI KASUS ANAK USIA 4-5 TAHUN DI KOBER LIL AULAD - Nurmala, Lela; Nugraha, Anggi Purwa; Mulyono, Nono (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2024)
This study aims at exploring the impact of optimizing reading corner to increase early childhood’s interest in reading and the effective strategies for integrating reading corners into learning. The study used a qualitative method under a case study approach and involving 14 early childhoods aged 4 - 5 and two teachers from Kober Lil Awlad, Ciamis Regency. The data were collected through in-depth interview and observation. The results revealed that optimizing reading corner can enhance early childhood’s interest in reading, creativity, and critical reasoning skills through several strategies implemented by the teachers. These strategies include updating the location and decoration of the reading corner, adding and arranging book collections, providing non-book support equipments, integrating the reading corner into learning activities, collaborating with parents, regular interactive activities, and the active role of teachers as inspirers, motivators, facilitators and evaluators to support early childhood’s interest in reading. In conclusion, optimizing the reading corner can improve early childhood’s interest in reading, creativity, and critical reasoning skills in 4 - 5 year old at Kobar Lil Awlad.